Mental health status and influencing factors of retired teachers - Luo, Pingyun; Liu, Yuanzhen; Pan, Xianjiang; Huang, Liyun (Frontiers in Public Health, 2024)
Introduction The wellbeing of retired teachers is often easily overlooked. This study aims to explore the mental health status and influencing factors of retired teachers. Method From October to December 2022, a convenient sampling survey was conducted on retired teachers using the Symptom Checklist 90 (SCL-90), mainly using the χ2-test and logistic regression analysis. Results A sampling survey was conducted on 353 retired teachers, with an overall positive detection rate of 16.1%. The five factors with the highest positive detection rate were found to be obsessive-compulsive disorder (30.3%), interpersonal sensitivity (21.5%), paranoia (20.1%), anxiety (19.3%), and others (19.3%). The detection rates for the five factors, namely psychosis, depression, hostility, terror, and somatization, are all below 19%. The data on sex (χ2 = 4.626, P = 0.043), professional title (χ2 = 17.670, P = 0.003), income (χ2 = 9.960, P = 0.041), life satisfaction (χ2 = 27.348, P = 0.000), family relationships (χ2 = 51.451, P = 0.000), and physical health status (χ2 = 50.361, P = 0.000) show that the difference in mental health among retired teachers is statistically significant. The multivariate binary logistic regression analysis revealed that family relationships, life satisfaction, and physical health were important factors leading to mental health problems among retired teachers. Discussion Retired teachers should cultivate a wide range of interests and hobbies, engage in regular physical exercise, develop healthy living habits, foster a positive family atmosphere, establish harmonious family relationships, promote community cultural construction, strengthen psychological intervention, and prevent psychological diseases.